1995
DOI: 10.1007/bf00172151
|View full text |Cite
|
Sign up to set email alerts
|

Structural analysis of the RH-like blood group gene products in nonhuman primates

Abstract: Rh-related transcripts present in bone marrow samples from several species of nonhuman primates (chimpanzee, gorilla, gibbon, crab-eating macaque) have been amplified by RT-polymerase chain reaction using primers deduced from the sequence of human RH genes. Nucleotide sequence analysis of the nonhuman transcripts revealed a high degree of similarity to human blood group Rh sequences, suggesting a great conservation of the RH genes throughout evolution. Full-length transcripts, potentially encoding 417 amino ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 51 publications
3
32
0
Order By: Relevance
“…A recent report by Salvignol et al (1995) indicated that 330-Ser was present in a chimpanzee cDNA, but the 33 l-Ile and the silent substitution appear to be human specific and, therefore, may have arisen since the divergence of humans and apes. Chimpanzees and gorillas do not show any species-specific residues, as no amino acids unique to all members of either species were found.…”
Section: Pcr Amplification Of Exon 7from Genomic Dnamentioning
confidence: 99%
“…A recent report by Salvignol et al (1995) indicated that 330-Ser was present in a chimpanzee cDNA, but the 33 l-Ile and the silent substitution appear to be human specific and, therefore, may have arisen since the divergence of humans and apes. Chimpanzees and gorillas do not show any species-specific residues, as no amino acids unique to all members of either species were found.…”
Section: Pcr Amplification Of Exon 7from Genomic Dnamentioning
confidence: 99%
“…Thus, the absence of reactivity of LOR-15C9 with these variants strongly suggests that exon 7 encoded sequence of RhD (amino acids 314-358) is critical for the binding of LOR-15C9. This conclusion was supported by the reactivity of LOR-15C9 with red cells of nonhuman primates: (i) the reactivity of the antibody with D gor -positive red cells of gorilla 'Mabeke' is correlated with the presence of three D-specific residues Asp 350 -Gly 353 -Ala 354 in the region encoded by exon 7 of Mabeke's Rh-like cDNA (Salvignol et al, 1995); (ii) the motif Asp 350 -Gly 353 -Ala 354 was absent from all chimpanzee Rh-like polypeptides (Salvignol et al, 1995) and all chimpanzee red cell samples were found LOR-15C9 negative.…”
Section: Discussionmentioning
confidence: 87%
“…Differences in the number of duplicated genes and pseudogenes have been reported in humans and chimpanzees. For example, chimpanzees have three copies of the RhD blood group gene (Westhoff and Wylie, 1996;Salvignol et al, 1995;Apoil and Blancher, 2000) and an additional triosephosphate isomerase pseudogene (Craig et al, 1991) in comparison to humans. The hominid lineage also underwent a duplication of V k immunoglobulin light-chain genes (Ermert et al, 1995).…”
Section: Gene Duplicationmentioning
confidence: 99%